Space Weather on the Surface of Mars: Impact of the September 2017 Events. Issue 11 (7th November 2018) - Hassler, D. M.; Zeitlin, C.; Ehresmann, B.; Wimmer‐Schweingruber, R. F.; Guo, J.; Matthiä, D.; Rafkin, S.; Berger, T.; Reitz, G.
Abstract: Although solar activity is declining as the Sun approaches solar minimum, a series of large solar storms occurred in September 2017 that impacted both Earth and Mars. This was the largest event seen on the surface of Mars by the Radiation Assessment Detector on the Mars Science Laboratory Curiosity rover since landing in 2012 and was also observed as Ground Level Enhancement 72 on Earth, making it the first event observed to produce a Ground Level Enhancement on two planets at the same time. We present Radiation Assessment Detector observations of the surface radiation environment since 2012 and discuss the impact of the September 2017 events on this environment and its implications for human exploration and for mitigating the risk of space radiation and space weather events for future manned missions to Mars. Key Points: On 11 September 2017, MSL RAD observed the strongest solar particle event seen on the surface of Mars since landing in 2012 Dose rates and neutral particle fluxes increased by factor of 2; proton and 4 He fluxes increased by factor of 30 and 10, respectively Integrated dose was only slightly greater than before the event, due to reduced quality factor during the event, and Forbush decrease after the event